The The influence of time management, self-confidence, and business capital on entrepreneurial stress among MSME food court vendors in Banjarmasin - Paulina Juliantri; Monry Fraicky Nicky Gillian Ratumbuysang; Syaripudin Bahar; Mahmudah Hasanah; Yandi Machmud (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
This study aims to examine the influence of time management, self-confidence, and business capital on entrepreneurial stress among MSME food court actors in Banjarmasin. The research involved 100 respondents selected using purposive sampling. A quantitative approach was applied using multiple linear regression analysis with SPSS. Data were collected through structured questionnaires that met validity and reliability requirements. The results indicate that, in part, time management and self-confidence do not have a significant effect on entrepreneurial stress, whereas business capital does. Simultaneously, all independent variables significantly influence entrepreneurial stress. The coefficient of determination (R²) indicates that the independent variables explain a portion of entrepreneurial stress. These findings suggest that external factors, particularly business capital, play a more dominant role compared to internal psychological factors in influencing entrepreneurial stress.